1999
DOI: 10.2135/cropsci1999.0011183x003900040046x
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Efficient Management and Utilization of Large Germplasm Collections

Abstract: To make effldent use of large germplasm collections, it is advisable to assemble a representative core collection and to evaluate the relationships among the traits studied. However, the assemblage of a core collection from very large germplasm collections is problematic. The computing resources needed to carry out genetic distance calculations and comparisons with commonly available programs is prohibitively large. The objects of this study were (i) to develop a method which assembles a core collection by max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 1 publication
1
54
1
1
Order By: Relevance
“…Of the 72 (36 genotypic and 36 phenotypic) correlations, 13 genotypic and seven phenotypic combinations were significant at 1% along with four genotypic and one phenotypic combinations was significant at 5% (Table 5). Skinner et al (1999) suggested only those correlation coefficients, which are greater than 0.70 or smaller than -0.70 as biologically meaningful so that 50% of the variation in one trait is predicted by the other. The seed trait pair showing such high correlation was 11 and all were positive.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 72 (36 genotypic and 36 phenotypic) correlations, 13 genotypic and seven phenotypic combinations were significant at 1% along with four genotypic and one phenotypic combinations was significant at 5% (Table 5). Skinner et al (1999) suggested only those correlation coefficients, which are greater than 0.70 or smaller than -0.70 as biologically meaningful so that 50% of the variation in one trait is predicted by the other. The seed trait pair showing such high correlation was 11 and all were positive.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence variants within FT homologs from sunflower (Helianthus annuus; Blackman et al, 2010), wheat (Yan et al, 2006), rice (Hagiwara et al, 2009), and Arabidopsis (Schwartz et al, 2009) have been shown to be important for flowering-time adaptation. Since there is significant variation in flowering time in different Medicago accessions (Skinner et al, 1999), it is possible that variation in the activity or expression of the various Medicago FT family members underlies some of this variation.…”
Section: Discussionmentioning
confidence: 99%
“…However, only correlation coefficients greater than 0.71 or smaller than -0.71 have been suggested to be biologically important (Skinner et al, 1999), as more than 50% of the variation in one trait is predicted by the other (Snedecor & Cochran, 1980). In our study, we found such important associations (at genotypic level) between days to 50% tasseling and days to 50% silking (0.99), plant height and ear height (0.99), plant height and leaf length (0.97), ear diameter and 1000 seed weight (0.77), and number of rows per ear and number of kernels per row (0.95).…”
Section: Discussionmentioning
confidence: 99%